Respuesta :

Answer:

The Solution is (3, 9)

Step-by-step explanation:

Given

[tex]4x-2y=-6[/tex]

[tex]3x+y=18[/tex]

Now by Using Cramer's Rule

Solving for x:

[tex]x= \frac{Dx}{D} =\frac{\begin{vmatrix}-6 & -2 &\\18 &1 &\end{vmatrix}}{\begin{vmatrix}4 & -2 &\\3 &1 &\end{vmatrix}} = \frac{-6+36}{4+6}=\frac{30}{10}=3[/tex]

Solving for y:

[tex]y= \frac{Dx}{D} =\frac{\begin{vmatrix}4 & -6 &\\3 &18 & \end{vmatrix}}{\begin{vmatrix}4 & -2 &\\3 &1 & \end{vmatrix}} = \frac{72+18}{4+6}=\frac{90}{10}=9[/tex]

The Solution is (3, 9)